Novel Echocardiographic Parameter Assessing Pulmonary Vascular Resistance in Patient with Acyanotic Congenital Heart Disease - Natadikarta, Muhammad Raihan Ramadhan; Cool, Charlotte Johanna; Khalid, Achmad Fitrah; Sukmadi, Norman; Martha, Januar Wibawa (Jurnal Kardiologi Indonesia, 2024)
Background Pulmonary vascular resistance (PVR) is an important variable in management of acyanotic congenital heart disease. Right heart catheterization (RHC) using impedance catheter remains gold standard for pulmonary vascular resistance (PVR) measurement. The ratio of peak tricuspid regurgitant velocity to the right ventricular outflow tract time-velocity integral (TRVmax/RVOTVTI) was presented as a reliable non-invasive method of estimating PVR. Recently, right ventricular 2-dimensional speckle tracking strain (RVGLS) was proven as a new promising parameter to evaluate PVR. This study performed to examine whether this new non-invasive variable ratio (TRVmax/RVGLS) provides clinically reliable method to determine pulmonary vascular resistance (PVR) obtained by echocardiography. Methods Right-heart catheterization and echocardiographic examination were performed in 56 patients with congenital heart disease. The ratio of TRVmax/RVOTVTI and TRVmax/RVGLS analysis performed using receiver-operating characteristic curve analysis, a cutoff value for the ratio was generated to determine PVR more than 5 WU. Results A TRVmax/RVOTVTI cutoff value of 0.21 provided a sensitivity of 77.1% and a specificity of 81% (CI 81% to 97.5%) and TRVmax/RVGLS cutoff value of -23.16 provided sensitivity of 74.3% and a specificity of 90.5% to determine PVR > 5 WU (CI 79.6% to 98.2%). Conclusions The echocardiography parameter (TRVmax/RVGLS) could serve as a dependable noninvasive method to predict PVR greater than 5 WU in acyanotic congenital heart disease patients.